The Immune Characteristics of the Epididymis and the Immune Pathway of the Epididymitis Caused by Different Pathogens - Zhao, Hu; Yu, Caiqian; He, Chunyu; Mei, Chunlei; Liao, Aihua; Huang, Donghui (Frontiers in Immunology, 2020)
The epididymis is an important male accessory sex organ where sperm motility and fertilization ability develop. When spermatozoa carrying foreign antigens enter the epididymis, the epididymis shows “immune privilege” to tolerate them. It is well known that a tolerogenic environment exists in the caput epididymis, while pro-inflammatory circumstances prefer the cauda epididymis. This meticulously regulated immune environment not only protects spermatozoa from autoimmunity but also defends spermatozoa against pathogenic damage. Epididymitis is one of the common causes of male infertility. Up to 40% of patients suffer from permanent oligospermia or azoospermia. This is related to the immune characteristics of the epididymis itself. Moreover, epididymitis induced by different pathogenic microbial infections has different characteristics. This article elaborates on the distribution and immune response characteristics of epididymis immune cells, the role of epididymis epithelial cells (EECs) and the epididymis defence against different pathogenic infections (such as uropathogenic Escherichia coli, Chlamydia trachomatis, and viruses to provide therapeutic approaches for epididymitis and its subsequent fertility problems.